Variants of the functional equation of Cauchy - Mačys, Juozas (Lietuvos matematikos rinkinys, 2004)
In this paper solution of the Cauchy functional equation and variants of it are considered.
Keywords: functional equation; Cauchy's equation; Cauchy's method